Characteristics and source appointment of atmospheric particulate mercury over East China Sea: Implication on the deposition of atmospheric particulate mercury in marine environment. (May 2017) - Duan, Lian; Cheng, Na; Xiu, Guangli; Wang, Fujiang; Chen, Ying
Abstract: Total Suspended Particulate (TSP) samples were collected at Huaniao Island in northern East China Sea (ECS) from March 2012 to January 2013. Chemical analysis were conducted to measure the concentration of total particulate mercury (TPM) and speciated particulate mercury including HCl-soluble particulate mercury (HPM), elemental particulate mercury (EPM) and residual particulate mercury (RPM). The bromine (Br) and iodine (I) on particles were also detected. The mean concentration of TPM during the study period was 0.23 ± 0.15 ng m −3, while the obviously seasonal variation was found that the concentrations of TPM in spring, summer, fall and winter were 0.34 ± 0.20 ng m −3, 0.15 ± 0.03 ng m −3, 0.15 ± 0.05 ng m −3 and 0.27 ± 0.26 ng m −3, respectively. The statistically strong correlation of bromine and iodine to HPM was only found in spring with r = 0.81 and 0.77 (p < 0.01), respectively. While the strongest correlations between EPM and bromine and iodine were found in winter with r = 0.92 (Br) and 0.96 (I) (p < 0.01), respectively. The clustered 72-h backward trajectories of different seasons and the whole sampling period were categorized into 4 groups. In spring, the clusters passed a long distance across the East China Sea and brought about low concentration of mercury due to the deposition of mercury over the sea. The cluster of air mass across the sea had low concentration of HPM in winter, which suggested that the oxidation of mercury in winter might be related to other oxidants. During the whole sampling period, the air mass from the north of China contributed to the higher concentration of TPM in Huaniao Island. Graphical abstract: Highlights: The seasonal patterns of TPM and speciated particle Hg are summarized. The relationships between halogens and mercuric species were analyzed. The cluster analysis was used to identify the transport pathways and potential sources.